2019
DOI: 10.1073/pnas.1907481116
|View full text |Cite
|
Sign up to set email alerts
|

A symmetric geometry of transmembrane domains inside the B cell antigen receptor complex

Abstract: B lymphocytes have the ability to sense thousands of structurally different antigens and produce cognate antibodies against these molecules. For this they carry on their surface multiple copies of the B cell antigen receptor (BCR) comprising the membrane-bound Ig (mIg) molecule and the Igα/Igβ heterodimer functioning as antigen binding and signal transducing components, respectively. The mIg is a symmetric complex of 2 identical membrane-bound heavy chains (mHC) and 2 identical light chains. How the symmetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Moreover, the association of CD79b with the α heavy Ig chain ( Fig. 3E ) essentially rules out any role for a poly-IgA receptor on NKB cells leading to monomeric IgA surface expression ( 34 , 35 ). Although CD79a is also expressed, staining was limited and likely a consequence of using a monoclonal antibody to a human epitope that may not be optimal for macaque antigen ( Fig.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, the association of CD79b with the α heavy Ig chain ( Fig. 3E ) essentially rules out any role for a poly-IgA receptor on NKB cells leading to monomeric IgA surface expression ( 34 , 35 ). Although CD79a is also expressed, staining was limited and likely a consequence of using a monoclonal antibody to a human epitope that may not be optimal for macaque antigen ( Fig.…”
Section: Discussionmentioning
confidence: 91%
“…This finding suggests that the skewing of NKB cell light chains is more similar to that of mucosal plasma cells ( 32 ) than that of peripheral blood B cells, which have a greater predominance of κ light chains ( 33 ). Since surface Ig expression is dependent on Ig heavy chain interaction with CD79 ( 34 , 35 ), we stained for CD79b expression. CD79b expression was associated with anti-IgA surface expression on NKB cells but not B cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For TCR, charged interactions deep within the TMD helices are critical for its assembly 10 . For BCR, the evolutionary conserved E/Q-X 10 -P motifs in Igα (E142-X 10 -P153) and Igβ (Q164-X10-P175) and the YS motifs (Y466-S467) in mIg define certain polar interactions within the membrane, albeit also asymmetrically instead of symmetrically as predicted 24,25,26,27 . The TCRα/µ incorporates three CD3 signalling dimers and thus forms an 8-helix bundle in the TCR TMD, with the α/β helices surrounded by helices of the CD3 components.…”
Section: Discussionmentioning
confidence: 92%
“…A previous analysis of mIg TMD sequences suggested that the side of the α-helix highly conserved in all mIg isotypes (TM-C) associates with TMDs of the Igα/β heterodimer, whereas the other side harbouring class-specific residues (TM-S) is involved in µHC dimerization and mIg oligomerization 24 . Our cryo-EM structure shows that this assignment is not correct as the central TM-C side mediates µHC dimerization and its neighbouring residues dominantly interact with Igα TMD and to a lesser extent Igβ TMD.…”
Section: Discussionmentioning
confidence: 99%
“…Equally, the conservation of a hydrophilic serine at position 304 in the teleost H lineage transmembrane domain sequences, and maybe also the partial conservation of a proline at position 290, suggest interaction of the TM domain with some other molecule. Examples of molecules believed to use a conserved serine/threonine or proline within the transmembrane domain for intermolecular protein binding are CD74 [54,55] and Igα [56], respectively. The identity of the molecules putatively interacting with the HAA TM/CY regions can only be guessed.…”
Section: Resultsmentioning
confidence: 99%